The Effect of Red Betel Leaf (Piper crocatum) and Moringa Leaf Extracts on Endometritis Levels in Aceh Cows - Rosmaidar Rosmaidar; Meutia Handayani; Fadillah Fadillah; Teuku Armansyah; Tongku Nizwan Siregar; Hafizuddin Hafizuddin; Husnurrizal Husnurrizal (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
This study aims to determine the ability of red betel leaf (Piper crocatum) or Moringa leaf extracts to reduce the endometritis level in Aceh cattle. In this study, six Aceh cows aged 3-5 years, weighing 150-250 kg from the Experimental Animal Technical Implementation Unit of Faculty of Veterinary Medicine of Syiah Kuala University were used. The cows were divided into two treatment groups, namely cows with endometritis that were given red betel leaf extract (T1) and cows with endometritis that were given Moringa leaf extract (T2). Examination of the endometritis levels was carried out before and after treatment using the White Side Test (WST) method. The collection of estrus cervical mucus was needed for the WST examination, and heat induction was performed with prostaglandin F2 alpha (PGF2α) at a dose of 25 μg. Collection of cervical mucus was performed 8-12 hours after the initiation of heat. All cows with endometritis were given intrauterine extracts of red betel leaves or Moringa leaves at a concentration of 20% every 24 hours for a week at a solution volume of 20 ml. The data were then analyzed using a paired t test. The mean endometritis levels before and after treatment on K1 vs. K2 were 3.0 and 1.7 vs. 2.7 and 2.7, respectively (P<0.05). It was concluded that red betel leaf extract at a concentration of 20% was more effective in reducing the endometritis level of Aceh cows than Moringa leaf extract.